Coming 2 America [videorecording (DVD)] - Barris, Kenya, 1974-; Blaustein, Barry W.; Sheffield, David, 1948-; Kanew, Justin; Murphy, Eddie, 1961-; Hall, Arsenio; Fowler, Jermaine; Jones, Leslie, 1967-; Morgan, Tracy, 1968-; Layne, KiKi; Headley, Shari, 1964-; Snipes, Wesley; et al. (Paramount Pictures, 2022)
Shortly before his father's death, Prince Akeem learns that he sired an illegitimate son during his last stay in the United States and now he has to return to Queens to retrieve him to ensure a male successor to the throne.